TINJAUAN HUKUM ISLAM TERHADAP NIKAH FASID DAN DAMPAKNYA (Studi Terhadap Putusan Hakim di Pengadilan Agama Bengkulu - Meiryana, Feity (UIN Fatmawati Sukarno Bengkulu, 2018)
The purpose of the research is to know the judge’s consideration, the impact of the judge’s decision and the review of Islamic law against the marriage of the fakid in the Religious Court of Bengkulu. Research type is normative. The research approach is the case approach. Data collection techniques used are literature techniques from primary legal materials and secondary legal materials. The analysis used is qualitative analysis. The result of the research is that the judge in deciding the case of marriage cancellation has been in accordance with the Laws Regulation, because the judge in this case is guided by the Compilation of Islamic Law and Positive Law. In addition, the impact of the decision of the cancellation of marriage is; since the issuance of the Decision of the Religious Courts that the marital relationship is abolished and is considered never to carry out the contract of marriage, while the child who has been born to the marriage remains guardian to his father and for the needs of his life is still the responsibility of his parents, especially the father. The inheritance of the cancellation of the marriage remains joint property. While fasid marriage in view of Islamic law is a marriage that must be canceled because of the terms or pillars of marriage is not met and violate the rules set by sharia law